EFFECT OF MEMANTINE AS N-METHYL D-ASPARTATE RECEPTOR ANTAGONIST ON CASPASE-9 LEVEL OF RETINAL GANGLION CELL IN METHANOL TOXIC OPTIC NEUROPATHY RAT MODEL: Oral Presentation - Experimental Study - Ophthalmologist - ANTONIA KARTIKA; Rusti Hanindyasari; Dianita Veulina Ginting; Pretyllayolamada (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Methanol toxic optic neuropathy (MTON) remains as a health issue in developing countries and there are no current definitive treatments. Accumulation of formic acid as metabolite of methanol causes mitochondrial dysfunction that can reduce ATP synthesis rate, disrupt axoplasmic transport, and elevate the reactive oxygen species (ROS). All of these mechanisms lead to the death of retinal ganglion cell (RGC) and optic nerve. RGC destruction in MTON has similar patterns with those that have been observed in glaucoma, ischemia, and trauma cases, that is through excessive activation of glutamate neurotransmitter via N-Methyl D-Aspartate receptors (NMDAR). Memantine is a NMDAR antagonist that inhibit the ion channel of NMDAR. This inhibitory effect of NMDAR by memantine is expected to reduce intracellular calcium level, prevent apoptosis of RGC, and prevent further mitochondrial dysfunction. Caspase-9 is essential to eliminate cells by executing apoptotic Objective: To observe the effect of Memantine on Caspase-9 level of RGC in Methanol-Intoxicated Rats. Methods : This experimental study was performed on 28 Methanol-Intoxicated Rats that are assigned into four treatment groups: K1 (MTON;enucleated day-3), K2 (MTON+Memantine; enucleated day-3), K3 (MTON; enucleated day-7), and K4 (MTON+Memantine; enucleated day-7). During the experiment, all groups were exposed to N2O:O2 gas and were given methanol orally. Caspase-9 level of RGC were measured immediately after enucleation. Results : The average of Caspase-9 level (ng/ml): K1=197,88±33,98; K2=205,64±63,66; K3=243,15±40,13; K4=150,08±119,60. The Caspase-9 level was significantly lower in K4 compared to K3 (p value =0.038). Conclusion : Memantine decrease the level of Caspase-9 of RGC in Methanol Toxic Optic Neuropathy rat model.